Personality-guided therapy in behavioral medicine - Harper, Robert G. (Personality-guided psychology / series editor Theodore Millon, 2004)
(from the jacket) In Personality-Guided Therapy in Behavioral Medicine, Harper integrates a broad research base on how personality type interacts with and affects the course of common medical conditions such as cancer, diabetes, and cardiovascular disease. Using Theodore Millon's personality-guided psychotherapy as a framework, he illuminates why and how patients with specific personality attributes interact with their health care providers, make lifestyle choices that affect the course of disease, make use of psychosocial supports, and cope with the demands of illness as well as treatment. Filled with practical guidance and strategies for treatment in a hospital or outpatient setting, this book will be of practical use to clinicians. Researchers will benefit from an understanding of the various personality disorders and their implications for prevention and treatment.